The Impact of The Companions’ Ijtihad on The Evolution of Islamic Law in Subsequent Eras - M Nasir; Alwis Tarusang (STAI DDI Makassar, 2024)
The research aims to encompass historical, legal, and methodological aspects in the development of Islamic law. The primary objectives of this research are. To understand the methods of ijtihad used by the companions of Prophet Muhammad (peace be upon him) and to assess the impact of their ijtihad on the development of Islamic law, both in the short term and the long term. The methodology used in this study is a comprehensive and systematic literature review regarding the impact of the Companions' ijtihad on the evolution of Islamic law. The process involves collecting, coding, and extracting data from relevant literature, (a) Thematic Coding: Code the main themes of each study, such as the methods of ijtihad used, their impact on Islamic law, and their adaptation by subsequent scholars. (b) Data Extraction: Collect specific data such as types of ijtihad, historical context, main findings, and legal implications. The ijtihad of the Companions has made a profound and lasting contribution to the evolution of Islamic law. Their methods and decisions not only addressed immediate legal needs but also established enduring principles that have guided Islamic jurisprudence through subsequent eras. This study highlights the significance of their contributions and the continuous relevance of their ijtihad in shaping the dynamic and evolving nature of Islamic legal thought. The implications of this study emphasize the enduring relevance of their legal methodologies and principles, providing valuable insights and guidance for contemporary Islamic jurisprudence and its application in the modern world.